Transcending Organization in Temporary Systems: Aesthetics' Organizing Work and Employment in Creative Industries - Iben Sandal Stjerne (Copenhagen Business School (CBS), 2016)
Because of their temporary nature, work and employment in project based organizations are different from what we used to see in traditional organizational forms. Temporary employment, entailing less stability within the organization changes how employment and work are organized. Temporary systems are organized by transcending organization that go beyond the individual firm and replaces what used to be organized inside the firm. Following several calls for further research on these topics, this dissertation is a small step along the way as it investigates how work and employment are organized in temporary systems that lack stability and formal order. It advances our understanding of transcending organization in creative industries by adopting a practice based perspective. Empirically, the dissertation presents an in-depth study of the Danish film industry, which is an extreme case of a project based industry wherein temporary organizing dominates and challenges people to organize employment and work in new ways. The study draws on both ethnographic work and interviews conducted in the period from 2009-2015. The data set consist of 40 in-depth interviews of career trajectories with successful film workers with different functional roles and six months of ethnographic study of film projects in the Danish film industry, in particular delving into the film project Antboy and its sequels.
hdl:10398/9395
Keywords: 650